2019
DOI: 10.14283/jpad.2019.31
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of Cognitive Health and Related Factors in Elderly at Risk for Developing Alzheimer’s Dementia: A Longitudinal Cohort Study

Abstract: Background: The CHARIOT PRO Main study is a prospective, non-interventional study evaluating cognitive trajectories in participants at the preclinical stage of Alzheimer’s disease (AD) classified by risk levels for developing mild cognitive impairment due to AD (MCI-AD). Objectives: The study aimed to characterize factors and markers influencing cognitive and functional progression among individuals at-risk for developing MCI-AD, and examine data for more precise predictors of cognitive change, particularly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Despite relatively numerous studies on the relationship between depression and cognitive decline, a few gaps exist in the literature. First, although depression is very common among elderly individuals ( 16 ), available studies are often limited to middle-aged people ( 17 ), clinical patients ( 18 ), and urban areas ( 19 , 20 ). In addition, longitudinal studies, which are essential to investigate the causal effect of depression on the onset of cognitive decline, are still insufficient ( 21 , 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite relatively numerous studies on the relationship between depression and cognitive decline, a few gaps exist in the literature. First, although depression is very common among elderly individuals ( 16 ), available studies are often limited to middle-aged people ( 17 ), clinical patients ( 18 ), and urban areas ( 19 , 20 ). In addition, longitudinal studies, which are essential to investigate the causal effect of depression on the onset of cognitive decline, are still insufficient ( 21 , 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Observational studies exploring the relationship between LBP and neurodegenerative diseases have been conducted before ( Broetz et al, 2007 ; Aggarwal et al, 2010 ; Miller et al, 2013 ; Udeh-Momoh et al, 2019 ; Silveira Barezani et al, 2020 ). Several studies reported a high occurrence of LBP during the non-interventional course of AD ( Udeh-Momoh et al, 2019 ), and the interventional diagnostic and therapeutic procedure of AD ( Landen et al, 2013 ; Alcolea et al, 2014 ). Similarly, LBP was a common complaint during the treatment of ALS ( Aggarwal et al, 2010 ; Miller et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Possible relationships between LBP and neurodegenerative diseases have been previously postulated ( Broetz et al, 2007 ; Aggarwal et al, 2010 ; Miller et al, 2013 ; Udeh-Momoh et al, 2019 ; Silveira Barezani et al, 2020 ). In a prospective cohort of 690 participants at the preclinical stage of AD ( Udeh-Momoh et al, 2019 ), back pain was among the most frequently occurring (3.0%) safety events, whereas in a recent cross-sectional study of 115 patients with sporadic PD ( Silveira Barezani et al, 2020 ), 58.3% of participants reported to have LBP. A higher prevalence of back pain in PD patients (75/101, 74.3%) when compared with age-matched control patients (35/132, 26.5%) was reported in another prior study ( Broetz et al, 2007 ).…”
Section: Introductionmentioning
confidence: 97%
“…Exclusion criteria included a dementia or MCI diagnosis, presence of any neurological or psychiatric condition, substance use disorder or the presence of reversible causes of dementia. Further details can be found elsewhere 27 .…”
Section: Methodsmentioning
confidence: 99%